2021
DOI: 10.1007/s00429-021-02267-y
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural changes in short-term learning of a continuous visuomotor sequence

Abstract: You will be contacted as soon as possible.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 129 publications
(221 reference statements)
1
5
0
Order By: Relevance
“…Our previous study (Jäger et al, 2022) found the right SMA to be relevant for sequence-specific learning using EC, as supported by structural data from the same cohort (Tremblay et al, 2021). The current results showed HE decreases in left SMA with the identified cluster spanning across both hemispheres, extending our findings to this region, which has been found relevant for right-hand tasks in prior studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our previous study (Jäger et al, 2022) found the right SMA to be relevant for sequence-specific learning using EC, as supported by structural data from the same cohort (Tremblay et al, 2021). The current results showed HE decreases in left SMA with the identified cluster spanning across both hemispheres, extending our findings to this region, which has been found relevant for right-hand tasks in prior studies.…”
Section: Discussionsupporting
confidence: 88%
“…Whole brain HE maps were computed before (on day 1) and after learning the task (on day 5) as well as 12 days after no additional training took place. The present data has been published in previous studies, which focused on measures of functional connectivity and white matter changes, respectively (Jäger et al, 2022 ; Tremblay et al, 2021 ). The majority of the methods have previously been described in detail in (Jäger et al, 2022 ) and will briefly be presented here.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…The dataset was acquired in the context of a longitudinal study, where the participants learned to perform a motor sequence. Descriptions of this data have previously been published (Huck et al, 2019;Jäger et al, 2021;Tremblay et al, 2021). Briefly, participants were trained on a motor task over a time period of 17 days.…”
Section: Scanning Protocolmentioning
confidence: 99%
“…One hour of neurofeedback training with motor imagery was associated with increased fractional anisotropy in the sensorimotor segment of the corpus callosum [ 95 ]. Learning a complex visuomotor sequence over five consecutive days came along with changes of WM microstructure in the tracts underlying the sensorimotor cortices [ 96 ].…”
Section: How Best Can the Motor Reserve Be Quantified?mentioning
confidence: 99%